PENERAPAN METODE MIND MAPING UNTUK MENINGKATKAN KEMAMPUAN MENULIS NARASI SISWA KELAS IV SD NEGERI 33 PAGARALAM - M. Pandu Bacharsyah; Wasidi Wasidi (UNIB Press, 2022)
The purpose of this study was to describe the improvement of students' narrative writing skills using the mind map method in grade IV SD Neger 33 Pagar Alam for the 2020/2021 academic year. This research is a classroom action research (PTK) which consists of 4 stages, namely planning, acting, observing, and reflecting. The research subjects were 21 students of grade IV SD Negeri 33 Pagar Alam. Based on the results of the study, it was found that the application of the mind map method could improve the writing skills of the sixth grade students of SD Negeri 33 Pagar Alam, this can be seen from the average value in cycle I and cycle II and classically it has increased in cycle II.